Chemical and mineralogical composition of ilmenite: Effects on physical and surface properties. (January 2015) - Mehdilo, Akbar; Irannajad, Mehdi; Rezai, Bahram
Highlights: Structural substitution of Mg and V improves the ilmenite flotation behavior. Fe 3+ ions sourced mainly from hemoilmenite exsolution enhance ilmenite floatability. Electrical resistivity has a higher correlation with IEP, floatability and lattice constants. Substituted and exsolved impurities do not affect the ilmenite magnetic properties. Abstract: Some physical and chemical properties of three ilmenite samples: IL-F (purchased from the mineral dealership of A and F Krantz), IL-Q (Qara-aghaj deposit, Iran) and IL-K (Kahnuj deposit, Iran) were studied. The substitution of different amounts of Mg, Mn and V in the crystal structure of ilmenite was identified by microprobe analysis. Different amounts of hemoilmenite exsolution were observed inside all three ilmenite samples using SEM, electron microprobe and X-ray diffraction analysis. Using these analytical techniques, titanite phase was found inside the IL-K ilmenite. The XPS analysis indicated that the contents of Fe 3+ are 5.66, 5.33 and 3.72% for IL-F, IL-Q and IL-K, respectively which are in good agreement with the amounts of hemoilmenite exsolution. Mg and V contents in the ilmenite crystal structure have a good negative correlation with lattice constants (LC), unit cell volume, crystallinity index, specific gravity and IEP, while the Mn content correlates positively with these parameters. The IEP determined as 4.2, 5.4 and 6.25 for IL-F, IL-Q and IL-K, respectively, has a negative correlation with Fe 3+ ions and ilmenite floatability. In comparison with magnetic susceptibility, the electrical resistivity of ilmenite has a higher correlation with surface properties (IEP and floatability), lattice constants, and unit cell volume.